(untitled) (Journal of the College of Basic Education, 2025)
The tourism sector is one of the most important sectors on various levels, as occupying leisure time is of paramount importance, linked to an individual’s mental health, revitalizing their energy, and enhancing community energy in various aspects. The research, entitled " Sustainable Tourism Industry at Al-Jubaish District in Dhi Qar Governorate 2025 Using Modern Technologies" highlights the existing natural and human potential, which has created a distinct natural environment that has become the focus of global attention. It has been included on the World Heritage List and the Ramsar Convention on Wetlands, giving it of great global importance. The research began with the main problem, which is (What are the natural and heritage environmental potentials that Al- Jubaish district has that are capable of developing and sustaining tourism activity?) In this research, we tried to answer this question by following several approaches, the most important of which is the descriptive and analytical approach to highlight the importance of the available potentials, as well as the regional approach to show the spatial distribution of existing and potential tourist sites in it. It relied on modern technologies in that, the most important of which are geographic information systems in explaining and determining the optimal location for them, as well as some analytical statistical programs such as the quadrilateral analysis (SWOT). Therefore, its importance comes from what the district possesses of great natural and human potentials that qualify it to be an important tourist destination at the level of Iraq and the world, the research aims to demonstrate the natural environmental potential and human resources that produced the cultural and heritage products in it and its role in achieving sustainable tourism development using modern technologies. The most important results reached by the research is that the district enjoys natural environmental resources represented by the presence of marshes and water bodies, the most important of which is Al-Hammar Marsh. The area of the district with its water bodies is (2,372) km2 and its population is (61,000) people. The area of the water bodies, including the marshes, is (900) km2. The region has climatic and environmental characteristics that distinguish it and make it a distinctive tourist destination that has been able, despite the weakness of the capabilities, to attract many tourists, whose numbers reach thousands monthly, whether they are local or foreign. The study area is home to many simple tourist activities such as resorts and marinas. The area suffers from a lack of necessary services such as water, sewage, transportation, and health services, as well as a lack of first-class hotels and restaurants that can receive visitors, except for one hotel built of mud and roofed with reeds and papyrus. After stating the current reality and applying the SWOT analysis, it became clear that the district enjoys strengths and opportunities that qualify it to be a distinctive tourist destination due to its picturesque nature and environment that can overcome weaknesses and threats. Therefore, the district is clearly and greatly qualified to be one of the tourist attractions that support the tourism sector in Iraq.